DOI: 10.17077/etd.tzjodhy2
|View full text |Cite
|
Sign up to set email alerts
|

Amish family care for children with chronic illnesses

Abstract: READER of the JOURNAL recently asked the following As regards the use of the word cmmc, why do we so often find a partitive where one would naturally expect a general noun? We fmd,-"Il fait comme Zes grands seigneurs." T h i s seems natural, but in one recent text I find,-"I1 est fragile c o m e dzc verre," and in another,-"Si les grenouilles dtaient grosses comme des bceufs, elles seraient bien laides." Surely all "verre" is "fragile" and all "bceufs" "gros" to a "grenouille." Just below this latter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 121 publications
(206 reference statements)
0
5
0
Order By: Relevance
“…When asked to describe why caregiving is important to them, all participants described the role of caregiver from a responsibility perspective and as a manifestation of their cultural values. Schuldigekeitt is a German word meaning duty or to do one's duty (Kueny, 2011), and participants typically paired one-word statements such as "privilege" and "gift " with a defi nition of what Schuldigekeitt means to the Amish (e.g., "responsibility, when we were young they took care of us and now that they are older…we should take care of them"). Th roughout the interviews, there was a clear declaration that participants "want to take care of our old people, not put them in a home" and "if at all possible, you want to keep at home. "…”
Section: Lived Experience Caring For Amish Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When asked to describe why caregiving is important to them, all participants described the role of caregiver from a responsibility perspective and as a manifestation of their cultural values. Schuldigekeitt is a German word meaning duty or to do one's duty (Kueny, 2011), and participants typically paired one-word statements such as "privilege" and "gift " with a defi nition of what Schuldigekeitt means to the Amish (e.g., "responsibility, when we were young they took care of us and now that they are older…we should take care of them"). Th roughout the interviews, there was a clear declaration that participants "want to take care of our old people, not put them in a home" and "if at all possible, you want to keep at home. "…”
Section: Lived Experience Caring For Amish Older Adultsmentioning
confidence: 99%
“…Th e exact numbers of Amish older adults and chronic disease prevalence is unknown, but most Amish individuals live in rural areas and are thought to have a similar health profi le to their rural counterparts. Evidence exists that Amish individuals are increasingly seeking health care outside of their community, especially for care of individuals with illness (Farrar, 2014;Kueny, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Critical ethnographers usually depend on coding data into descriptive or functional categories to identify, compare, and transfer findings relating to a group of people beyond its local context. Also known as "ethnographic analysis," this analytical method is a free-form, inductive approach that requires the ethnographer to immerse themselves in the data, get to know and understand it, and then develop coding schemes that move from a descriptive level to a more analytic level (Atkinson, 2007;Kueny, 2011). Although critical ethnographers may borrow from other analytical traditions to meet their study objectives, such as interpretive phenomenological analysis (Walby, 2013), thematic analysis (Sharp et al, 2018), narrative analysis (Jobling, 2019), and Leininger's method for qualitative data analysis (Salman et al, 2018), their underlying goal remains the same; namely, to better understand culture for purposes of emancipation.…”
Section: Critical Clinician-researchers In Mental Healthmentioning
confidence: 99%
“…These prescriptive to‐do lists fail to acknowledge the socioeconomic, historic, and political contexts and the potential ethnocentric perspective of the health care provider, as recommended by a conceptual position of cultural safety. Recently, researchers observed that the Amish are increasingly seeking health care services outside of their communities, particularly for people with chronic illnesses (Cates, ; Farrar, ; Gillum, Staffileno, Schwartz, Coke, & Fogg, ; Kueny, ). There is little scientific research with the Amish about their relationship with the Western health care system.…”
Section: Amish and Lg Mennonite Communities’ Historical Context And Ementioning
confidence: 99%